Integration of Geolocation and Real-Time Data for Optimizing Boarding House Search in Mobile Applications - Ardi, Abdullah; Aufar, Yazid; Syaputra, Aldo Eko; Saputra, Memed (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2025)
This study focuses on the development and evaluation of a mobile-based boarding house search application that integrates geolocation technology and real-time data, with implementation in the Banjarmasin area. The application is designed to help users easily find boarding houses based on their current location, while providing up-to-date information on room availability, pricing, and facilities. Testing showed that the application performs optimally across various devices, with an average response time of 2.5 seconds and efficient resource usage. A survey involving 100 users in Banjarmasin revealed that 94% of respondents were satisfied with the ease of navigation and the accuracy of the information provided. The implementation of real-time data significantly increased user trust by up to 90%, while the location-based search feature accelerated the boarding house search process by 40%. In addition, the application contributed to a 20% increase in boarding house occupancy rates in Banjarmasin after three months of use by property owners. This research offers a significant contribution to the development of mobile applications in the housing sector.